Dialogical Parenting in the Qur'an: A Literature Review on Transformative-Prophetic Character Education - Ashief El Qorny; Ayatullah El Haqqi; M. Jamal; Muhammad Syakur; Sumarjoko; Husna Nashihin (At Turots: Jurnal Pendidikan Islam, 2025)
This research aims to construct a transformative and prophetic model of children's character education, based on the dialogue of Nabawiyah's parenting as reflected in the Qur'an. Using a qualitative research method based on library research within the framework of a critical paradigm, this study analyzes several verses that contain the dialogue of the Prophets with their children (such as the dialogue of Ibrahim and Ismail in QS. As-Shaffat: 102, Nuh with his son in QS. Hud: 42–43, Ibrahim with Azar in QS. Maryam: 42–47, Luqman with his son in QS. Luqman: 13–19, and others). Hermeneutic analysis and critical discourse are applied to synthesize the pedagogical values of these texts. The study's results identified six models of educational dialogue: moral awareness, preventive ethics, spiritual intimacy, transmission of universal values, ideological criticism, and cross-generational inheritance of faith. These findings criticize normative approaches in Islamic education that tend to ignore children's participation and reflection. This study contributes to developing a dialogical, participatory, and prophetic Islamic character education framework relevant to the principles of contemporary critical pedagogy.